Evaluation of selected elements of fitness and physiological diagnostics of military pilots as a factor in flights safety - Wochyński, Zbigniew (Frontiers in Physiology, 2025)
The author of the publication drew attention to factors that threaten the safe performance of a military aviation mission. The aim of the article is to present an effective method for diagnosing psychomotor skills, monitoring physical fitness and selecting pilots of highly maneuverable aircraft, as well as selected exercise markers of high diagnostic value for assessing the adaptation (efficiency) of the pilots’ body. First, the focus was on the practical direction of preventing aviation accidents. Based on many years of research on cadet pilots, the author developed the Aviation-Synthetic Efficiency Test (ASET), which aims to select candidates for aviation and assess the performance of an anti-overload maneuver involving appropriate skeletal muscles. The test was used to monitor the training process in order to obtain an optimized physical load on the body. The factor strengthening the implementation of an effective pilot training process was the assessment of the behavior of the WS lipid index as confirmation of the training effects in the G-strain centrifuge test. The author attributes special diagnostic value to lipid indices for pilots of highly maneuverable aircraft. A diagnostic and training device was developed and used to monitor the special training process in terms of assessing the psychomotor level of pilots in extreme conditions of the pilot’s work environment. Studies were also conducted in the special training process on special aviation gymnastics devices (SAGI). Physiological and biochemical indicators were used in these studies, emphasizing the high diagnostic value in relation to the physical fitness and health of pilots. The aspects of the research presented in this article contribute to the pilots’ compliance with the balance between the performance of tasks and their physical capabilities, which undoubtedly increases flight safety.